Use of linked electronic health records to evaluate cardiovascular risk prediction models in Ontario, Canada. (2018) - Sivaswamy, Atul; Khan, Anam; Tu, Karen; Azizi, Paymon; Ko, Dennis; Tu, Jack
No abstract available